Coorg, Tables, Vol-XV - Elwin, D.H. (Karnataka, 1941)
Area houses and population, Variation in population during fifty years, Towns and villages classified by population, Towns arranged territorially with population by communities, Variation in population of Selected Tribe.
Keywords: Coorg; Tables